Poverty Reduction Analysis of Foreign Tribe Communities in Kutai Kartanegara Regency - Bambang Arwanto (Eduvest - Journal of Universal Studies, 2022)
Rural poverty is a very complex synthesis, both in terms of the potentially poor population, the type of poverty and the process that causes poverty itself. Based on these arguments, this study aims to show that the treatment of regional development programs in poverty alleviation efforts cannot actually be carried out uniformly. This study is intended to provide an analytical model to increase the productivity of the poor with a certainty that rural poverty is unique and specific, by approaching isolated tribal groups. The research uses a case study approach, what policies are most effective to increase the productivity of the poor, isolated tribes, data collection for the unit of analysis is carried out using the PRA (Participatory Rural Appraisal) method to explore the problems developed in participatory research, where researchers only act as facilitator while community groups and tribal tribal institutions play an active role in analyzing and assessing the problems they experience. The results of the study confirm that the policies that need to be implemented in an effort to increase the productivity of the isolated tribal community are carried out through several alternative policies, namely; rehabilitation of forest resources, increasing human resources of isolated tribes, as well as controlling the shrinkage of potential cultivated areas